Combination Of Schroth Exercise With Brace On Acceleration Of Cobb Angle Changes In Case Of Scoliosis : Literature Review - Nabilah Putri Mahdani; Riza Pahlawi (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
To evaluates the effectiveness of schroth exercise with a brace to accelerate changes in the cobb angle in cases of idiopathic scoliosis. This study is a literature review study with a narrative method. The research was conducted by tracing and analyzing articles relevant to the topics raised. The data used in this research is secondary data. Sources of secondary data obtained in the form of articles or journals relevant to the topic using the Pubmed, Proquest, and Google Scholar databases using the keywords "idiopathic scoliosis OR adolescent" AND "schroth exercise OR brace" AND "cobb angle OR quality of life" the researchers found 2,262 journals that match these keywords. The research journals were then screened based on the title and abstract, as many as 20 journals were excluded because they did not match the inclusion. After conducting a critical appraisal of 10 published journals, the appraisal instrument used was JBI Critical Appraisal Tools and two critical appraisals were carried out. 5 journals that did not meet the inclusion criteria were excluded. So that 5 journals were synthesized. The journal found based on this research found that the combination of Schroth exercise and brace was effective in accelerating changes in the Cobb angle in cases of idiopathic scoliosis.